자궁절제술을 받은 여성과 배우자의 성생활 - 김진경; 고효정; Kim, Jin-Kyung; Koh, Hyo-Jung (여성건강간호학회지, 2001)
The purpose of this study was to provide basic data from confirming factors that could help nurses tailor counseling program for married couples who were facing the prospect of a hysterectomy. A descriptive design was used to study a total of 81 married couples(total of 162 subjects) between 2 to 18 months after hysterectomy, due to a benign gynecology disease at a University Hospital in Daegu by questionnaires from March, 1999 to June, 2000. This study used Sexual Knowledge Measurement of Koo, Ja-sung(1996), Sexual Attitude Scales of Hudson, Murphy and Nurius(1994), Sexual Attitude Measurement of Jang, Soon-bok(1989), Sexual Activity Questionnaires of Thiriaway, Fallowfield and Cuzick(1996) modified and supplemented by advice of experts in order to measure sexual knowledge, sexual attitude and sexual activity, and Sexual Function Inventory of Derogatis(1979) translated by Jang, Soon-bok(1984) was used to measure sexual satisfaction of the subjects. For data analysis, the study executed $x^2$-test, t-test, ANOVA, Pearson correlation and multiple regression in accordance with the purpose of study by SPSS/PC+ WIN 10.0 program. Also this study obtained Cronbach's alpha for examination of reliability. The results are as follows : 1) The sexual knowledge of the husband was higher than that of the wife after hysterectomy by showing the mean 11.27(${±}2.72$) in case of the wife and the mean 11.57(${±}2.28$) in case of the husband, but there was no statistically significant difference(t=.681, p=.497). 2)The sexual attitude of the husband was more liberal than that of the wife after hysterectomy by showing the mean 3.25(${±}.48$) in case of the wife and the mean 3.42(${±}.48$) in case of the husband, and there was statistically significant difference(t=2.399, p=.018). 3)There was no statistically significant difference between the score of sexual activity of wife and husband by period elapsed after hysterectomy. 4)There was no statistically significant difference between the score of sexual satisfaction of wife and husband by period elapsed after hysterectomy. 5)The wife subjects showed positive correlation among sexual knowledge, sexual attitude, sexual activity and sexual satisfaction. The husband subjects showed positive correlation only between sexual knowledge and sexual activity, sexual activity and sexual satisfaction, sexual attitude and sexual satisfaction, sexual knowledge and sexual satisfaction. There was a positive correlation between the sexual knowledge, sexual attitude, sexual activity and sexual satisfaction of the wife and husband. 6)Only the variable of sexual activity among factors of sexual satisfaction of the wife subjects showed the statistical significance(F=52.452, p<0.001), while variables of sexual attitude (F=20.360, p<0.001) and sexual activity (F=14.142, p<0.05) among factors of sexual satisfaction of the husband subjects showed a statistical significance.